Performance Assessment in Teaching EFL Reading in Indonesia: Viewed From First Language (L1) Use to Check Learners’ Comprehension - Candra Jaya (Bandar Lampung University (UBL), 2014)
In spite of widespread use of English in English Foreign Language learning, the use of First Language (L1) in EFL classroom is still indispensable to teachers and learners. The aim of this qualitative study was to discover teaching EFL reading in senior high school students that was assessed retelling activity (RTA) as a performance assessment by utilizing L1 as a checking device. Teaching EFL reading class is based upon the standards of performance assessment and the principles of the strands of learning English course that are incorporated in L1 use to check learners’ comprehension. Two instruments were used in this study including questionnaire and interview of which each question covered behavior aspect and attitudinal aspect The findings of questionnaires showed that (1) almost all students encountered learning difficulties , consisting of vocabulary, pronunciation, grammar, translation, and text comprehension, in EFL use in their performance assessment, (2) almost all students encountered learning facilities, consisting of L1 meaning familiarity and text understanding, by L1 use in their performance assessment. These are supported by students’ interviews that described (1) their learning difficulties in EFL use that consisted of word meaning and text understanding, (2) their learning facilities in L1 use that consisted of L1 meaning familiarity and text understanding.